Application of Direct-sequencing Peptide Proteomics to the Characterization of Antagonistic (Endogenous and Exogenous) Proteins in Cereal Grains - Koziol, Adam (Université d'Ottawa / University of Ottawa, 2013)
The cereal seed plays a crucial role in society – both in the “food as medicine” paradigm, but also in food security. It is the starch and proteins present in the seed that lend it importance in these dissimilar anthropomorphic activities. This thesis investigation first characterized the post-translational processing of the potential diabetogen, wheat globulin-3. Globulin-3-like peptides were observed primarily in the embryo. These peptides varied significantly in their molecular masses and isoelectric points, as determined by two dimensional electrophoresis and immunoblotting. Five major polypeptide spots were sequenced by mass spectrometry, allowing for the development of a model of the post-translational events contributing to the globulin-3 processing profile. Three separate investigations of starch granules from different cereal species were performed. In the first series of experiments, pathogen-susceptible maize kernels were injected with either conidia of the fungal pathogen Fusarium graminearum or sterile water controls. Proteins in the desiccated fungal remnants on the surface of the kernels as well as in the endosperm and embryo tissues of the control and infected kernels were isolated and these proteomes were sequenced using tandem mass spectrometry. Approximately 250 maize proteins were identified. These proteins were classified into functional categories. There was an increased representation of defense proteins in the both the embryo and endosperm tissues of infected maize samples. The proteome of the fungal remnants was composed of 18 proteins. Several of these proteins were categorized as being involved in the metabolism of plant-sourced molecules, or in stress response. The second series of experiments detail the investigation of commercially prepared rice and maize starches using tandem mass spectrometry. The majority of identified proteins, in both rice and maize samples, were involved in either carbohydrate metabolism or storage. Markers for seed maturity and for starch mobilization were also documented. Finally, the third series of experiments investigated the non-host proteomes present in commercially-prepared starches. Non-host proteins from a variety of species, including Homarus americanus were found in the starch samples. This documentation of H. americanus proteins in these starch samples may have food safety implications with regards to shellfish allergies.
Keywords: globulin; diabetes; starch granule-associated proteome; food security; translational medicine; plant/pathogen interactions